REVIEW OF QUALITY OF LIFE IN THE COVID-19 ERA - Alejandra Navarrete Quezada; Cruz García Lirios; José Marcos Bustos Aguayo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The quality of life has been a highly studied process from a psychological perspective. In this sense, the present work set out to establish an explanatory model of life satisfaction to discuss the importance of other disciplines in the investigation of resources that satisfy individuals. Once the relationships between the factors derived from the theoretical framework and the review of the literature were explained, a cross-sectional study was carried out with a non-probabilistic sample of 100 students. Once established the validity and reliability of the instrument that measured life satisfaction, expected abilities, opportunity expectations, trust relationships, perception of justice, appreciation of the environment, context norms and perceived resources. From a structural model, the perception of resource availability indirectly determined life satisfaction through the context norms. The results were compared with the findings reported in the state of knowledge as well as discussed from theoretical frameworks used.